Measuring shape fluctuations in biological membranes. (12th May 2016) - Monzel, C; Sengupta, K
Abstract: Shape fluctuations of lipid membranes have intrigued cell biologists and physicists alike. In the cellular context, their origin—thermal or active—and their physiological significance are open questions. These small incessant displacements, also called membrane undulations, have mostly been studied in model membranes and membranes of simple cells like erythrocytes. Thermal fluctuations of such membranes have been very well described both theoretically and experimentally; active fluctuations are a topic of current interest. Experimentally, membrane fluctuations are not easy to measure, the main challenge being to develop techniques which are capable of measuring very small displacements at very high speed, and preferably over a large area and long time. Scattering techniques have given access to fluctuations in membrane stacks and a variety of optical microscopy based techniques have been devised to study membrane fluctuations of unilamellar vesicles, erythrocytes and other cells. Among them are flicker spectroscopy, dynamic light scattering, diffraction phase microscopy and reflection interference contrast microscopy. Each of these techniques has its advantages and limitations. Here we review the basic principles of the major experimental techniques used to measure bending or shape fluctuations of biomembranes. We report seminal results obtained with each technique and highlight how these studies furthered our understanding of physical properties of membranes and their interactions. We also discuss suggested role of membrane fluctuations in different biological processes.